ANALISIS MULTIVARIAT FAKTOR PENENTU PARTISIPASI ORANG TUA DALAM PENDIDIKAN ANAK DI KABUPATEN PURWAKARTA - Muhamad Najua; Ahmad Pandu W; Muhammad Sulthon N. M; Bima Ananto (Jurnal Manajemen Pendidikan, 2026)
Parental participation is a critical determinant of student success, yet participation levels vary significantly in industrial regions like Purwakarta. This study aims to analyze the simultaneous and partial effects of parental motivation, parent-school communication, and family environment on parental participation (academic and non-academic) using a multivariate approach. This quantitative research employed a survey method with purposive sampling of 50 parents in Purwakarta. Data were analyzed using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS) with SmartPLS software, which is suitable for analyzing smaller sample sizes. The multivariate analysis reveals that family environment is the most dominant factor, significantly influencing both academic participation (β=0.435, p=0.012) and non-academic participation (β=0.361, p=0.025). Parent-school communication significantly affects academic participation (β=0.302, p=0.022) but not non-academic participation (β=0.275, p=0.061). Interestingly, parental motivation alone does not have a significant effect on either academic (β=0.251, p=0.081) or non-academic participation (β=0.090, p=0.524). This study highlights the "intention-behavior gap" in an industrial society context, proving that a supportive home environment and effective communication are more critical drivers of participation than motivation alone.